1998
DOI: 10.1063/1.872850
|View full text |Cite
|
Sign up to set email alerts
|

Results from current drive experiments on the Helicity Injected Torus

Abstract: The Helicity Injected Torus [T. R. Jarboe, Fusion Technol. 15, 7 (1989)] is a low aspect ratio tokamak that is formed and sustained by coaxial helicity injection with no transformer. Toroidal plasma currents of over 200 kA have been achieved with electron temperatures in the 100 eV range and electron density between 1019 and 1020 m−3. The major radius is 0.3 m and the minor radius is 0.2 m. New results from equilibrium and stability analysis of the external magnetic diagnostics and new results from the Transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 14 publications
2
64
0
Order By: Relevance
“…Despite the large values of cyclotron harmonic involved (9)(10)(11)(12)(13)(14), significant wave damping is expected at large values of the ion beta. Acceleration of neutral beam injected 80 keV ions to 140 keV has been observed.…”
Section: Ov/2-2mentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the large values of cyclotron harmonic involved (9)(10)(11)(12)(13)(14), significant wave damping is expected at large values of the ion beta. Acceleration of neutral beam injected 80 keV ions to 140 keV has been observed.…”
Section: Ov/2-2mentioning
confidence: 99%
“…• The application of coaxial helicity injection [11,12] (CHI) has yielded a toroidal current of up to 400 kA, with observations of n=1 MHD activity that may be a prerequisite for closed flux surface formation.…”
Section: Inner Pfs and Oh Coilmentioning
confidence: 99%
See 2 more Smart Citations
“…These devices also employed passive wall stabilization for equilibrium control and confirmed that CHI could be used in the presence of an external toroidal. Later HIT was rebuilt as the HIT-II experiment, which extended CHI to a true ST device by employing 28 poloidal field coils for equilibrium control instead of from image currents induced on copper walls [14]. HIT-II produced substantial plasma currents (200 kA) using transformer action or using CHI [15].…”
Section: Introductionmentioning
confidence: 99%